LOS oligosaccharide modification enhances dendritic cell responses to meningococcal native outer membrane vesicles expressing a non‐toxic lipid A. (6th November 2013) - Jones, Hannah E.; Copland, Alastair; Hamstra, Hendrik Jan; Cohen, Jonathan; Brown, Jeremy; Klein, Nigel; van der, Peter; Dixon, Garth
Summary Outer membrane vesicles (OMV) are released by many bacteria, and contain immunogenic antigens in addition to harmful inflammatory factors, like lipopolysaccharides. Chemically detoxified OMV have been used in vaccines against Neisseria meningitidis (Nm); however, little is known about their interaction with antigen presenting cells. In this study, we investigated the interaction of Nm OMV with human dendritic cells (DC) to gain further understanding of their biological activity. We engineered a novel serogroup B Nm that is unencapsulated (siaD), expresses pentacylated lipid A (lpxL1), hence conferring reduced toxicity, and expresses an lgtB oligosaccharide structure designed to target OMV to DC via DC‐SIGN. We show that the lgtB moiety is critical for internalization of NOMV by DC. Furthermore, the lgtB moiety significantly enhances DC maturation, IL‐10 and IL‐23 production in the presence of a pentacylated lipid A. While different DC phenotypes were observed for each NOMV, this had little effect on Th1 and Th2 cell differentiation; however, lgtBsignificantly increased Th17 cell expansion in the presence of pentacylated lipid A. We believe that lpxL1/lgtB NOMV should be considered further as a vaccine vector, particularly considering the importance of lgtB in antigen uptake and further human studies on antigen‐specific responses should be considered.